2014
DOI: 10.1007/s12011-013-9877-3
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary Chromium(III) Propionate Complex Does Not Protect Against Insulin Resistance in High-Fat-Fed Rats

Abstract: Improper eating habits such as high-fat or high-carbohydrate diets are responsible for metabolic changes resulting in impaired glucose tolerance, hyperinsulinemia, insulin resistance, and ultimately diabetes. Although the essentiality of trivalent chromium for humans has been recently questioned by researchers, pharmacological dosages of this element can improve insulin sensitivity in experimental animals and diabetic subjects. The aim of the study was to assess the preventive potential of the supplementary ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 46 publications
0
17
0
1
Order By: Relevance
“…The data obtained by Herring et al [ 32 ] strongly suggest that long-term (15-month) Cr3 supplementation does not significantly affect metabolic responses in blood glucose concentration to glucose and insulin in male Wistar rats consuming a normal diet or high-fat, high-carbohydrate cafeteria-style diet. Also Król et al [ 33 ] confirmed that supplementary Cr3, given in the dosages 0.6 and 3 mg· kg −1 b.m. for 8 weeks, did not affect serum glucose, insulin and HOMA-IR index and serum lipid indices, except TAG (tended to decrease) in rats fed high-fat diet.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The data obtained by Herring et al [ 32 ] strongly suggest that long-term (15-month) Cr3 supplementation does not significantly affect metabolic responses in blood glucose concentration to glucose and insulin in male Wistar rats consuming a normal diet or high-fat, high-carbohydrate cafeteria-style diet. Also Król et al [ 33 ] confirmed that supplementary Cr3, given in the dosages 0.6 and 3 mg· kg −1 b.m. for 8 weeks, did not affect serum glucose, insulin and HOMA-IR index and serum lipid indices, except TAG (tended to decrease) in rats fed high-fat diet.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, Clodfelder et al [ 4 ] did not observe adverse effects of Cr3 on the Fe status when given to healthy rats or to the animals with type 2 diabetes for 24 weeks as an aqueous solution at doses of 250–1000 μg of Cr· kg −1 b.m. In contrast, Cr3 supplementary in doses 10 and 50 mg· kg −1 diet for 8 weeks increased kidney Fe and spleen Cu contents but did not affect Zn status in rats fed with high-fat diet [ 33 ]. The studies by Shara et al [ 38 , 39 ] demonstrated that long-term supplementation with complex Cr(III) with niacin did not affect the metabolism of Fe in the rat (as assessed by the content of Fe in the serum, TIBC, RBC, haemoglobin and selected indicators of blood morphology).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the results obtained by Herring et al [ 54 ] suggest that long-term (15 months) Cr3 supplementation does not significantly impact metabolic responses in blood glucose concentration to glucose and insulin in male rats’ intake of a high-fat diet, high-carbohydrate cafeteria-style diet or normal diet. By contrast, Cr3 supplementation at doses of 10 and 50 mg kg −1 diet for 8 weeks increased the kidney Fe content in rats fed a high-fat diet [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Administering CGA alone without CrIII fully restored body weight and glucose tolerance, but not insulin tolerance or fed glucose levels, which remained significantly different from RD-fed mice treated with water alone. While few studies failed to detect an insulin-sensitizing role for chromium in humans [ 34 ] and rats fed a high-fat diet for 8 weeks [ 35 ], several others highlighted its metabolic benefits. For instance, it has been shown to reduce hyperglycemia and attenuate insulin resistance in part, by inhibiting the ubiquitin-proteasome pathways mediating degradation of insulin receptor substrate 1 and 2, critical mediators of insulin signaling [ 22 ].…”
Section: Discussionmentioning
confidence: 99%